Variable Exponent Central Morrey Estimates for Multilinear Bochner-Riesz Operators (Analysis in Theory and Applications, 2025)
We prove the boundedness of multilinear Bochner-Riesz operator on central Morrey spaces with variable exponents. Moreover, we also show that the variable exponent Lipschitz commutator of Bochner-Riesz operator are bounded on above spaces. As applications, we also obtain the bounds of the commutators generated by $λ$-central BMO functions and Bochner-Riesz operators on central Morrey spaces with variable exponents.
Keywords: Multilinear Bochner-Riesz operator; commutator; central Morrey space with variable exponent; boundedness.